Azacitidine Nanoemulsion Formulation and Characterization for the Tumor Treatment Suppressor Genes Activity in Myeloid Leukemia Cell Lines (Asian Journal of Pharmaceutics (AJP), 2025)
The present study aimed to develop and evaluate an Azacitidine (AZA) nanoemulsion to enhance absorptionand therapeutic effectiveness. AZA, a pyrimidine nucleoside analogue, interferes with DNA methylation by inhibitingDNA methyltransferase and acts as a cytidine antimetabolite incorporated predominantly into RNA. Althoughclinically effective as an anticancer drug, its low absorption limits its utility. Materials and Methods: Nanoemulsionswere formulated using distilled water, co-surfactants (Transcutol P, plysorbate 80), AZA, and selected oils suchas oleic acid. Various water-in-oil nanoemulsion systems were prepared by high-speed homogenization. Theformulations were evaluated for stability, Fourier transform infrared (FTIR) compatibility, pH, thermodynamicstability, viscosity, and in vitro drug release profiles. Results and Discussion: The optimized nanoemulsion displayedfavorable physicochemical characteristics, including acceptable pH, viscosity, and thermodynamic stability. FTIRanalysis confirmed the absence of major drug-excipient interactions. In vitro studies showed improved drugrelease compared to conventional formulations. The nanoemulsion demonstrated significant inhibitory activity(85.37%), approaching that of methotrexate (89.09%), suggesting its potential cytotoxic effect. Conclusion: Thedeveloped AZA nanoemulsion exhibited enhanced release and inhibitory activity, indicating improved therapeuticpotential. These findings support its possible application as a treatment strategy for myeloid leukemia cell lines,with additional studies warranted to confirm its histone deacetylase inhibitory effects.